Nusyuz in the Era of Social Media: Reinterpreting Wife Behavior in a Modern Context - Hendra Wijaya; Intan Permatasari (Indonesian Journal of Islamic Law, 2023)
This research reexamines the concept of nusyuz in the context of the social media era, highlighting how digitalization affects the dynamics of household relationships. Traditionally, nusyuz refers to the behavior of a wife who leaves the house without her husband's permission. However, in the digital era, this definition has expanded to include various forms of online behavior that challenge authority or norms within the household. Using qualitative and quantitative methods, this research explores how nusyuz behavior is expressed in online interactions and how this affects household stability. The research results show that intensive and uncontrolled use of social media can trigger conflict and disharmony, expanding the traditional boundaries of nusyuz into the digital realm. These findings urge the need for digital education and adaptive policies to address new challenges arising from digital interactions in husband and wife relationships. This research offers in-depth insight into the adaptation of social and cultural norms in the face of shifts in power and self-expression brought about by the digital era.